Medication self-management skills and cognitive impairment in older adults hospitalized for heart failure: A cross-sectional study - Howell, Erik H (SAGE Open Med, 2017)
BACKGROUND: Cognitive impairment is highly prevalent among older adults (aged ≥65 years) hospitalized for heart failure and has been associated with poor outcomes. Poor medication self-management skills have been associated with poor outcomes in this population as well. The presence and extent of an association between cognitive impairment and poor medication self-management skills in this population has not been clearly defined. OBJECTIVE: We assessed the cognition of consecutive older adults hospitalized for heart failure, in relation to their medication self-management skills. METHODS: We conducted a cross-sectional study of older adults (aged ≥65 years) who were hospitalized for heart failure and were being discharged home. Prior to discharge, we assessed cognition using the Mini-Cog. We also tested patients’ ability to read a pill bottle label, open a pill bottle safety cap, and allocate mock pills to a pill box. Pill allocation performance was assessed quantitatively (counts of errors of omission and commission) and qualitatively (patterns suggestive of knowledge-based mistakes, rule-based mistakes, or skill-based slips). RESULTS: Of 55 participants, 22% were found to have cognitive impairment. Patients with cognitive impairment tended to be older as compared to those without cognitive impairment (mean age = 81 vs 76 years, p = NS). Patients with cognitive impairment had a higher prevalence of inability to read pill bottle label (prevalence ratio = 5.8, 95% confidence interval = 3.2–10.5, p = 0.001) and inability to open pill bottle safety cap (prevalence ratio = 3.3, 95% confidence interval = 1.3–8.4, p = 0.03). While most patients (65%) had pill-allocation errors regardless of cognition, those patients with cognitive impairment tended to have more errors of omission (mean number of errors = 48 vs 23, p = 0.006), as well as more knowledge-based mistakes (75% vs 40%, p = 0.03). CONCLUSION: There is an association between cognitive impairment and poor medication self-management skills. Medication taking failures due to poor medication self-management skills may be part of the pathway linking cognitive impairment to poor post-discharge outcomes among patients with heart failure transitioning from hospital to home.